2015
DOI: 10.1080/09540121.2015.1114992
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with antiretroviral treatment uptake and adherence: a review. Perspectives from Australia, Canada, and the United Kingdom

Abstract: International focus on reducing onward HIV transmission emphasizes the need for routine HIV testing and early uptake of antiretroviral treatment (ART). Strategic targets have been set for 2020 to achieve the goal of 90% of people infected with HIV diagnosed, 90% of identified cases on treatment, and 90% of persons on treatment virally suppressed (90-90-90). It is vital to understand the complexity of factors influencing a person's treatment decisions over time and the context which may enable better adherence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 49 publications
0
44
2
Order By: Relevance
“…This may be due to the fact that HIV testing uptake for both males and females in Kenya is highest between the ages of 25-29 years and mostly take place in VCT hence increased linkage to HIV care and management among this age group [28]. Of note are that these findings are in contrast with previous studies in indicating that found that young age is associated with low uptake of ART [29,30], suggesting that that there may be context-specific barriers to ART uptake that may persist despite changes to clinical guidelines encouraging early uptake.…”
Section: Discussioncontrasting
confidence: 56%
“…This may be due to the fact that HIV testing uptake for both males and females in Kenya is highest between the ages of 25-29 years and mostly take place in VCT hence increased linkage to HIV care and management among this age group [28]. Of note are that these findings are in contrast with previous studies in indicating that found that young age is associated with low uptake of ART [29,30], suggesting that that there may be context-specific barriers to ART uptake that may persist despite changes to clinical guidelines encouraging early uptake.…”
Section: Discussioncontrasting
confidence: 56%
“…7,8 From the available evidence, an average rate of 24.8% of nonadherence to medication has been reported in most of the patients having chronic diseases 9 ; however, the level of ART adherence among PLHIV is higher compared to most of the other chronic diseases. 10 Previously published studies reported multiple barriers for optimal adherence to ART in both developed and developing countries, [11][12][13][14] which could be categorized into patient-related, medication-related, and health system-related factors. 15 As these barriers vary across settings, identification of the factors responsible for nonadherence to ART and contextualization of these factors will be helpful in designing and developing intervention strategies to improve adherence to ART.…”
Section: Introductionmentioning
confidence: 99%
“…However, symptoms like fatigue, cognitive failure and sleep disorders should also be considered as variables related to low compliance. Therefore, we investigated the frequency of symptoms associated with depression, self-reported psychosocial and treatment-related factors, in a sample of patients with failure to the first line of HAART [14]. …”
Section: P006mentioning
confidence: 99%